Interventions to increase facility births and provision of postpartum care in sub-Saharan Africa: a scoping review - Camara, Bienvenu Salim (Reprod Health, 2021)
BACKGROUND: Most maternal deaths occur during the intrapartum and peripartum periods in sub-Saharan Africa, emphasizing the importance of timely access to quality health service for childbirth and postpartum care. Increasing facility births and provision of postpartum care has been the focus of numerous interventions globally, including in sub-Saharan Africa. The objective of this scoping review is to synthetize the characteristics and effectiveness of interventions to increase facility births or provision of postpartum care in sub-Saharan Africa. METHODS: We searched for systematic reviews, scoping reviews, qualitative studies and quantitative studies using experimental, quasi experimental, or observational designs, which reported on interventions for increasing facility birth or provision of postpartum care in sub-Saharan Africa. These studies were published in English or French. The search comprised six scientific literature databases (Pubmed, CAIRN, la Banque de Données en Santé Publique, the Cochrane Library). We also used Google Scholar and snowball or citation tracking. RESULTS: Strategies identified in the literature as increasing facility births in the sub-Saharan African context include community awareness raising, health expenses reduction (transportation or user fee), non-monetary incentive programs (baby kits), or a combination of these with improvement of care quality (patient’s privacy, waiting time, training of provider), and or follow-up of pregnant women to use health facility for birth. Strategies that were found to increase provision of postpartum care include improvement of care quality, community-level identification and referrals of postpartum problems and transport voucher program. CONCLUSIONS: To accelerate achievements in facility birth and provision of postpartum care in sub-Saharan Africa, we recommend strategies that can be implemented sustainably or produce sustainable change. How to sustainably motivate community actors in health interventions may be particularly important in this respect. Furthermore, we recommend that more intervention studies are implemented in West and Central Africa, and focused more on postpartum. PLAIN ENGLISH SUMMARY: In in sub-Saharan Africa, many women die when giving or few days after birth. This happens because they do not have access to good health services in a timely manner during labor and after giving birth. Worldwide, many interventions have been implemented to Increase the number of women giving birth in a health facility or receiving care from health professional after giving birth. The objective of this study is to synthetize the characteristics and effectiveness of interventions that have been implemented in sub-Saharan Africa, aiming to increase the number of women giving birth in a health facility or receiving care from health professional after birth. To proceed with this synthesis, we did a review of studies that have reported on such interventions in sub-Saharan Africa. These studies were published in English or French. The interventions identified to increase the number of women giving birth in a health facility include community awareness raising, reduction of health expenses (transportation or user fee), non-monetary incentive programs (baby kits), or a combination of these with improvement of care quality (patient’s privacy, waiting time, training of provider), and or follow-up of pregnant women to use health facility for birth. Interventions implemented to increase the number women receiving care from a health professional after birth include improvement of care quality, transport voucher program and community-level identification and referrals to the health center of mothers’ health problems. In sub-Saharan Africa, to accelerate increase in the number of women giving birth in a health facility and receiving care from a health professional after, we recommend interventions that can be implemented sustainably or produce sustainable change. How to sustainably motivate community actors in health interventions may be particularly important in this respect. Furthermore, we recommend the conduct in West and Central Africa, of more studies targeting interventions to increase the number of women giving birth in a health facility and or receiving care from a health professional after birth.